Pengembangan Media Layanan Informasi Menghadapi Perubahan Masa Pubertas bagi Siswa Sekolah Dasar - Firdayati, Fitri; Zen, Ella Faridati; Flurentin, Elia (Jurnal Kajian Bimbingan dan Konseling, 2016)
This research aims to produce a product in the form of information service media "dealing with changes in puberty" for elementary school students. The research method used is research and development adapted from the Borg and Gall development model with the following procedures: (1) planning; (2) product development; (3) product testing; (4) final product revision. Product trial data is analyzed quantitatively and qualitatively. Based on the results of the product trial assessment, it can be concluded that the product is very appropriate, very useful, very easy and very interesting theoretically and practically, so it can be used as a medium for guidance in dealing with changes during puberty.